Advertising communication in the professional analysis of an linguistic expert - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article analyzes modern parameters of advertising communication in the context of linguistic expertise and legal linguistics. Advertising is considered as an information product, intended to form and maintain the opinion of advertising consumers, to influence the recipient for marketing purposes, and therefore may become a subject of analysis of linguist-expert. Advertising communication is often interpreted as a powerful tool of influence on the mass consciousness, which leads to legal evaluation of the texts of advertising. The author defines professional limits of the linguist-expert who works with the advertising text, as well as described parameters of conflict in the advertising, its status in the legislative field and media reality. It is proposed to separate a special type of linguistic expertise of the advertising text (by functional-communicative parameter), which allows further search of the media linguist and legal linguist on the mentioned problem. Special attention is paid to the legal status of linguistic expertise of the advertising text, which is regulated by a number of laws of Ukraine ("About advertising", "About information", "About printed mass media (press) in Ukraine", etc.) and accompanying legal documents, regulations, agreements about international cooperation and others. The attention is focused on different types of advertising (informational, image, explanatory, reminding, etc.) and types, legally correlated (external, internal, social, commercial, etc.) texts. The legislative established types of advertising – conscientious and unscrupulous, discriminatory, comparative, etc., which language characteristics become the subject of analysis of linguist-expert are also commented. Thus, advertising as a powerful source of verbal and non-verbal manipulation strategies, which can be misled by potential consumers, is considered not only from the position of media analysts, but also legal linguistics and linguistics expertise.